The difficulties of employing e-learning in Iraqi universities as seen by professors. - Wid Dawood Qasim ALtimemi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
This study aimed to identify the difficulties of employing e-learning in Iraqi universities as seen by the professors, and to know the impact of university, gender, and specialization on the education process.